2017
DOI: 10.1111/brv.12378
|View full text |Cite
|
Sign up to set email alerts
|

Structure, function, and regulation of mitofusin‐2 in health and disease

Abstract: Mitochondria are highly dynamic organelles that constantly migrate, fuse, and divide to regulate their shape, size, number, and bioenergetic function. Mitofusins (Mfn1/2), optic atrophy 1 (OPA1), and dynamin-related protein 1 (Drp1), are key regulators of mitochondrial fusion and fission. Mutations in these molecules are associated with severe neurodegenerative and non-neurological diseases pointing to the importance of functional mitochondrial dynamics in normal cell physiology. In recent years, significant p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
138
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(142 citation statements)
references
References 197 publications
(258 reference statements)
3
138
0
1
Order By: Relevance
“…Mfn1 and Mfn2 are mitochondrial outer membrane tethering proteins that are essential for mitochondrial fusion. Since Mfn2 has been shown to also localize to the ER, it has been proposed that it serves an additional role in ER-mitochondria tethering 22,28 . The mitofusins are enriched in cells at inter-mitochondrial contact sites through homotypic (Mfn1-Mfn1) or heterotypic (Mfn1-Mfn2) interactions 22,49,50 .…”
Section: Tethers Are Concentrated At Inter-organelle Contactsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mfn1 and Mfn2 are mitochondrial outer membrane tethering proteins that are essential for mitochondrial fusion. Since Mfn2 has been shown to also localize to the ER, it has been proposed that it serves an additional role in ER-mitochondria tethering 22,28 . The mitofusins are enriched in cells at inter-mitochondrial contact sites through homotypic (Mfn1-Mfn1) or heterotypic (Mfn1-Mfn2) interactions 22,49,50 .…”
Section: Tethers Are Concentrated At Inter-organelle Contactsmentioning
confidence: 99%
“…Contact sites represent only a small proportion of the overall surface area of an organelle, but they serve several fundamental functions, including being the sites of inter-organelle exchange of lipids, ions, ROS and other small molecules [17][18][19][20][21] . Contact sites also play an important role in organelle inheritance and fission 17,[20][21][22][23][24][25][26][27][28] . Even though known tethering, effector, and regulatory proteins involved in contact site organization have been uncovered, how contact sites assemble and whether they exhibit selforganizational properties of lipids and proteins is unclear 17 .…”
Section: \Body Introductionmentioning
confidence: 99%
“…Currently, over 100 dominant mutations in the MFN2 gene have been reported in CMT2A patients though how these mutations lead to disease is still largely unknown. The challenges in MFN2 research are that MFN2 regulates mitochondrial fusion and a plethora of cellular functions such as mitochondrial dynamics, transport, mtDNA stability, lipid metabolism and survival (Chandhok et al, 2018). In addition, gain-of-function and loss-of-function mutations are reported that affect different aspects of cellular functions (Chandhok et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…29 Mitochondrial fusion is the merging of two mitochondria to form one functional entity, while mitochondrial fission refers to its division into two. 30 Fission is increased under nutrient rich conditions as well as with dying cells. A threestep process that includes organelle approximation, mitochondrial outmembrane tethering/fusion, and IMM fusion under control of mitofusion 1, 2 (Mfn1 and Mfn2), and dynamin-related GTPases.…”
Section: Mitochondria In Depressionmentioning
confidence: 99%